Risk factors and outcomes of SLE Patients with Lupus Nephritis Class III, IV and V treated at Hospital Tengku Ampuan Afzan, Kuantan - Mohd Zainuddin, Mohammad Nuriman; Ramli, Norazsida; Seman, Mohd Ramli (2017)
Lupus nephritis (LN) is a serious complication of systemic lupus erythematous (SLE) and the possible risk factors for the disease progression are not very well understood. In this study we aimed to determine the response to treatment and identify the potential risk factors associated with the response. A hospital record review and single centre study has been carried out that includes patients with Class III, IV and V LN, who underwent renal biopsy and were treated at Department of Nephrology, HTAA for at least one year. Secondary data from patients' medical record such as demographic data; gender, race, and clinical data; proteinuria, serum creatinine, comorbidities and type of treatment were collected as the independent risk factors. Out of 54 patients of LN, 19 patients (35.2%) were classified under Class III/ III+V LN, 28 patients (51.9%) Class IV/ IV+V LN and seven patients (13%) Class V LN. Response to induction treatment showed six patients (11.1%) had no response, 23 patients (42.6%) had complete remission and 25 patients (46.3%) with partial remission. Hypoalbuminemia and anaemia were identified as the potential risk factors associated with the response to induction treatment (p = 0.045) and (p = 0.016) respectively. Besides, other factors like gender, race, serum creatinine, comorbidities and type of treatment were not significantly associated with the response towards treatment. In conclusion, only hypoalbuminemia and anaemia associated with the response of the treatment. The treatment provided was considered as effective since only 6 cases of patients did not respond to treatment throughout the 54 cases reviewed.